Bulky hinge bracelet: inspired by traditional batik / Tuan Muhammad Anas Tuan Abdullah Sanusi - Tuan Abdullah Sanusi, Tuan Muhammad Anas (2022)
It has unique batik design that is suitable for Bulky Hinge Bracelet.